Investigating homicide offender typologies based on their clinical histories and crime scene behaviour patterns. Issue 3 (19th September 2019) - Abreu, Valeria; Barker, Edward; Dickson, Hannah; Husson, Francois; Flynn, Sandra; Shaw, Jennifer
Abstract : Purpose: The purpose of this paper is to identify offender typologies based on aspects of the offenders' psychopathology and their associations with crime scene behaviours using data derived from the National Confidential Enquiry into Suicide and Safety in Mental Health concerning homicides in England and Wales committed by offenders in contact with mental health services in the year preceding the offence ( n =759). Design/methodology/approach: The authors used multiple correspondence analysis to investigate the interrelationships between the variables and hierarchical agglomerative clustering to identify offender typologies. Variables describing: the offenders' mental health histories; the offenders' mental state at the time of offence; characteristics useful for police investigations; and patterns of crime scene behaviours were included. Findings: Results showed differences in the offenders' histories in relation to their crime scene behaviours. Further, analyses revealed three homicide typologies: externalising, psychosis and depression. Practical implications: These typologies may assist the police during homicide investigations by: furthering their understanding of the crime or likely suspect; offering insights into crime patterns; provide advice as to what an offender's offence behaviour might signify about his/her mental health background. Findings suggest information concerning offender psychopathology may be useful for offender profiling purposes in cases of homicide offenders with schizophrenia, depression and comorbid diagnosis of personality disorder and alcohol/drug dependence. Originality/value: Empirical studies with an emphasis on offender profiling have almost exclusively focussed on the inference of offender demographic characteristics. This study provides a first step in the exploration of offender psychopathology and its integration to the multivariate analysis of offence information for the purposes of investigative profiling of homicide by identifying the dominant patterns of mental illness within homicidal behaviour.